Vietnam : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This paper reviews economic developments in Vietnam during 1992-96. Economic growth was recorded at 8-9 percent during 1992-94, rising to a 9 1\2 percent annual rate in 1995 and the first half of 1996. Investment has been rising steadily over the past few years, owing in part to foreign investment, which increased to 9 percent of GDP in 1995 and continued to rise strongly in 1996. Vietnam's foreign trade has also expanded and diversified rapidly, with both imports and exports growing at double-digit annual rates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet